"Lie to me"—Oxytocin impairs lie detection between sexes. (October 2017) - Pfundmair, Michaela; Erk, Wiebke; Reinelt, Annika
Highlights: We examine how the hormone oxytocin affects lie detection. It decreases the ability to correctly classify other-sex statements as truths/lies. This effect may hint to its underlying mechanism as a catalyst for social adaption. Abstract: The hormone oxytocin modulates various aspects of social behaviors and even seems to lead to a tendency for gullibility. The aim of the current study was to investigate the effect of oxytocin on lie detection. We hypothesized that people under oxytocin would be particularly susceptible to lies told by people of the opposite sex. After administration of oxytocin or a placebo, male and female participants were asked to judge the veracity of statements from same- vs. other-sex actors who either lied or told the truth. Results showed that oxytocin decreased the ability of both male and female participants to correctly classify other-sex statements as truths or lies compared to placebo. This effect was based on a lower ability to detect lies and not a stronger bias to regard truth statements as false. Revealing a new effect of oxytocin, the findings may support assumptions about the hormone working as a catalyst for social adaption.